Financial education: the challenges of training educators of young learners - Ditta, Aline Wanderley Camisassa; Ramirez, Rodrigo Avella; Roberto Junior, Francisco de Sousa (Educação Matemática Debate, 2024)
This paper aims to investigate the current scenario of how Financial Education is taught by teachers at an institution that trains young learners, in order to propose a continuing education program in Financial Education. It is considered essential that teachers have knowledge acquired from both training and practical experience. The methodology employed was applied research, with a qualitative approach, using data collection and analysis, as well as thematic analysis. The study presents a scenario in which the importance of Financial Education in the lives of young learners is recognized, but identifies that the lack of teacher training is an obstacle. This challenge can be overcome through continuing education and communities of practice to train them in Financial Education.